2022
DOI: 10.1039/d1qm01622a
|View full text |Cite
|
Sign up to set email alerts
|

ADA′DA small molecule acceptors with non-fully-fused core units

Abstract: Two ADA’DA small molecule acceptors, IDTBT-4F and IDTP-4F, with non-fully-fused core units were developed. The DA’D core units were facilely prepared via Stille coupling of D and A’ fused-ring building...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Recently, a number of A-D-A 0 -D-A and A-D-D 0 -D-A type NFAs have been reported where electron rich IDT and electron deficient INCN moieties are centred around a third component, of either electron rich (D 0 ) or electron deficient (A 0 ) character. [62][63][64][65][66][67] Efficiencies of OPVs employing such materials have been reported between 2.7 and 11.9%, where the PBDB-T polymer was used as the electron donating species in the highest performing devices. 62 Overall, the NFAs centred around an electron deficient moiety have proven more successful than those with an electron rich moiety.…”
Section: Synthesis and Molecular Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a number of A-D-A 0 -D-A and A-D-D 0 -D-A type NFAs have been reported where electron rich IDT and electron deficient INCN moieties are centred around a third component, of either electron rich (D 0 ) or electron deficient (A 0 ) character. [62][63][64][65][66][67] Efficiencies of OPVs employing such materials have been reported between 2.7 and 11.9%, where the PBDB-T polymer was used as the electron donating species in the highest performing devices. 62 Overall, the NFAs centred around an electron deficient moiety have proven more successful than those with an electron rich moiety.…”
Section: Synthesis and Molecular Designmentioning
confidence: 99%
“…40,41 Nevertheless, the overall performance of these materials remains modest compared to other non-carborane IDT-INCN flanked materials reported to date. [62][63][64][65][66][67] Although the open-circuit current (V OC ) values of the devices were high at around 0.93 V, the short-circuit current density (J SC ) remained relatively low, ranging from 5.36 to 7.40 mAcm À2 , and J-V curves exhibited non-ideal behaviours with fill factors between 37 and 43%.…”
Section: Device Performancementioning
confidence: 99%
“…Previously, our group demonstrated that fused-ring aromatic lactones (FRAL) are efficient building blocks for high-performance copolymer donors. [50][51][52][53][54][55][56][57] In this work, we report the synthesis of a copolymer donor PBDTTPTP by using a novel tetracyclic bislactone unit, thieno[2 0 ,3 0 :5,6]pyrano [3,4d]thieno [3,2-b]pyran-4,9-dione (TPTP). Thanks to the strong electron-withdrawing properties and good coplanarity of TPTP, PBDTTPTP shows a relatively small E opt g of 1.65 eV, a deep HOMO level and good hole mobility, and exhibits good performance in STOPVs.…”
Section: Introductionmentioning
confidence: 99%